Prevalence of contagious bovine pleuropneumonia (CBPP) in north-east Peninsular Malaysia - M., Zarina; Saad, Mohd Zamri; Hassan, Latiffah; Salisi, Mohd Shahrom; A., Azri; O., Norlida (2015)
Contagious Bovine Pleuropneumonia (CBPP) is a highly infectious disease of cattle that is caused by Mycoplasma mycoides subsp. mycoides Small Colony (MmmSC). It is one of the diseases recognized by the OIE that needs to be controlled or eradicated through surveillance system. The objective of this study was to establish the prevalence of CBPP among the cattle population in the north-eastern states of the Peninsula Malaysia. A study involving cattle from selected farms in the two north-eastern states was performed. Kota Bharu Veterinary Regional Laboratory (RVL) received a total of 2,584 serum samples from 157 cattle farms between 2011 and 2013. These samples were tested for CBPP using the competitive ELISA (c-ELISA) kit to detect the organism specific antibodies. The animal-level prevalence ranged between 4% (43/882) in Terengganu and 10% (178/1702) in Kelantan whereas the herd prevalence ranged between 26% (20/76) in Terengganu and 37% (30/81) in Kelantan. The overall animal-level prevalence was 8% (221/2584) and the overall herd-level prevalence was 31% (50/157) for CBPP in the two states.